The Power of the Media to Influence Public Opinion by Setting the Agenda (Texas Journal of Multidisciplinary Studies, 2023)
There is abundant evidence that the media significantly shapes public opinion and policy in a given country. People learn not only the facts about current events from the news but also the relative importance of specific issues by observing how much coverage they receive. The prominence of a story in a newspaper's front page layout, other front page displays, enormous headlines, etc., all indicate how important a story is that day. Salience can also be inferred from television news, including the lead-in story, time spent on the topic, etc. The significance of each issue is effectively communicated through the repetition of these cues across multiple days. The news media can direct the public's focus on the relatively few problems that ultimately shape public opinion.